Corrosion Behavior of Recycling Al- Alloy Based Metal Matrix Composites Reinforced by Nano particles - Abdulkader, Niveen Jamal; Jasim, Nibras Saeed; Hashim, Fadhil Abbas (Kurdistan Journal of Applied Research, 2017)
The present work aims to preparation and investigation of the corrosion behavior of recycling Al alloy based metal matrix composite reinforced with nano SiC with weight percentage (2%, 4%, 6%, and 8%) and particle size 52 nm were evaluated. The composites were fabricated using liquid metallurgy (stir casting process). The corrosion rates of composites were calculated using potentiostatic measurements in 3.5% NaCl solution.. The results showed that Al/SiC nanocomposites have higher corrosion resistance than aluminum matrix.The corrosion resistance was found to be increased by increasing of the weight percentage of the nanoparticles The Al/8% nano (SiC)P composites exhibited the highest corrosion resistance among all the investigated nanocomposites. The microstructure indicate that the strong interfacial bonding between the matrix alloy and reinforcement.